Promoción de Salud Bucal y Gingival en niños de 10 a 12 años en la Institución Educativa José Jiménez Borja 2019 - Moreno Gutiérrez, Severino (Universidad Privada de Huancayo Franklin Roosevelt, 2021)
El presente estudio tuvo como objetivo determinar la efectividad de la promoción en salud bucal y gingival en escolares de 10 a 12 años de la I.E José Jiménez Borja.2019. Se realizó un estudio experimental, prospectivo, longitudinal y analítico de tipo cuantitativo, y la muestra estuvo constituida por 54 niños del grupo control y 54 niños del grupo experimental. Los resultados evidenciaron que, del total de escolares del grupo experimental, el 100% presentó IHO regular en el pretest y del total de escolares del grupo control el 94,4% presentó IHO regular en el pretest. Del total de escolares del grupo experimental, el 55.6% presentó IHO bueno en el postest y el 100% del grupo control presentan IHO en el postest. Del total de escolares del grupo experimental, el 79.9% presentó encía normal en el pretest; y del total de escolares del grupo control, el 61,1% presentó encía normal

The aim of this study was to determine the effectiveness of oral and gingival health promotion in schoolchildren between 10 and 12 years of age at the José Jiménez Borja School. 2019. An experimental, prospective, longitudinal and analytical quantitative study was carried out, and the sample consisted of 54 children in the control group and 54 children in the experimental group. The results showed that, of the total number of schoolchildren in the experimental group, 100% presented regular IHO in the pretest and of the total number of schoolchildren in the control group, 94.4% presented regular IHO in the pretest. Of the total number of schoolchildren in the experimental group, 55.6% presented good IHO in the post-test and 100% of the control group presented good IHO in the post-test. Of the total number of schoolchildren in the experimental group, 79.9% presented normal gingiva in the pretest; and of the total number of schoolchildren in the control group, 61.1% presented normal gingiva
promotion of Oral and Gingival Health in children from 10 to 12 years old in the Educational Institution José Jiménez Borja 2019
Keywords: Efectividad; Promoción de la salud bucal; Salud Gingival; https://purl.org/pe-repo/ocde/ford#3.02.14